INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM TRADISI ROKAT TASE’ SEBAGAI MEDIA PENDIDIKAN KARAKTER DI MASYARAKAT PESISIR PASEAN PAMEKASAN - Muhammad Dani Edi Irwan; Muliatul Maghfiroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Based on the phenomena that occur amidst the development of the times and the flow of modernization, the existence of the Rokat Tase’ tradition often experiences a shift in values and is even starting to be abandoned by the younger generation. This study aims to; First, describe the process of internalizing the values of Islamic Religious Education in the Rokat Tase’ tradition. Second, the role of the Rokat Tase’ tradition as a medium for character education. Third, the supporting and inhibiting factors for the internalization of the values of Islamic Religious Education in the Rokat Tase’ tradition in the coastal community of Pasean Pamekasan. The Rokat Tase’ tradition is a culture of fishing communities that is carried out as a form of gratitude to Allah SWT for the sustenance and safety given, as well as an effort to ask for blessings in life. This study uses a qualitative approach with a phenomenological research type. Data were obtained through observation, interviews, and documentation involving religious leaders, community leaders, the implementing committee, and the local community. The results of the study show that; First, the internalization of the values of Islamic Religious Education in the Rokat Tase’ tradition is carried out through various religious activities such as religious studies, reading the Qur'an, tahlil, istighasah, group prayers, and alms. The internalized values include religious values, gratitude, trust (Tawakal), social concern, mutual cooperation, togetherness, and responsibility. Second, the Rokat Tase’ tradition serves as a medium for character education that is able to shape the religious, social, cultural character, and independence of coastal communities. Third, supporting factors for the internalization of these values include support from religious and community leaders, high social solidarity, and a religious community environment. Inhibiting factors include the influence of modernization, low understanding of the meaning of tradition among some communities, limited funding, differences in religious views, and minimal involvement of the younger generation. Thus, the Rokat Tase’ tradition not only functions as a local cultural heritage, but also as an effective means of instilling Islamic Religious Education values and shaping the character of the coastal community of Pasean Pamekasan.